Buffelgrass production under various establishment methods in the "Sertão" region, Pernambuco, Brazil - de Albuquerque, Severino G.; Soares, José Givaldo G.; de Oliveira, Martiniano C.; Salviano, Luiz Mauricio C. (Pesquisa Agropecuaria Brasileira, 1994)
A trial was set up in a "Caatinga" vegetation area, to compare methods of buffelgrass (Cenchrus ciliaris L.) establishment. It was made up of 12 treatments, in a 2 x 2 x 3 factorial [2 woodland clearing methods (Slashing vs Clearing by bulldozer); 2 types of seedbed preparation (Plowing and disking vs no preparation); and 3 modes of seeding (Pits with seeds not covered vs pits with seeds covered vs broadcasting)]. It was started in September 1978 by woodland clearing, followed by grass seeding in January 1979. Evaluations in April 1979 and April 1980 showed no difference among seeding modes on buffelgrass production. There was effect of seedbed preparation on buffelgrass production (1,87 vs 0,26 t/ha in 79; 4,87 vs 1,63 t/ha in 80). Slashing was superior to clearing by bulldozer. There was interaction between clearing modes and seedbed preparation. Buffelgrass production in 1980 was superior to 1979 (3,24 vs 1,06 t/ha). The native grass production was very low in comparison to forbs, even when there was no establishment of buffelgrass in the first year.